Review on NSM CFRP Strengthened RC Concrete Beams in Shear - Majid M. A. Kadhim; Mohammed J. Altaee; Ali Hadi Adheem; Ali Chabuk; Nadhir Al-Ansari (Advances in Civil Engineering)
The use of NSM FRP strengthening of concrete structures has become an attractive option to retrofit the existing structures against shear and flexure. This paper reviews only the utilization of NSM for shear in previous review articles. A database of tests of NSM strengthened beams in shear is presented to evaluate the existing design formulations of calculating the NSM contribution in shear. These formulations were in agreement with the experimental results in the database. Further research topics are also identified such as the shape of NSM FRP bars, combined effects of existing steel stirrups, and NSM FRP reinforcement and analytical formulations.